Clinical application of sugammadex in renal impairment: pharmacokinetics and pharmacodynamics - Hao-Wei Lee; Pao-Shan Chen; Min-Jia Li; Chih-Shung Wong (Frontiers in Pharmacology, 2026)
Sugammadex, a modified γ-cyclodextrin, rapidly and predictably reverses aminosteroid neuromuscular blockade by directly encapsulating rocuronium and vecuronium, thereby avoiding the cholinergic adverse effects associated with acetylcholinesterase inhibitors. Because both free sugammadex and the sugammadex–rocuronium complex are eliminated predominantly through renal excretion, the use of sugammadex in patients with severe renal impairment remains a topic of debate. This review summarized current evidence on sugammadex by exploring its molecular mechanisms, pharmacokinetic and pharmacodynamic properties, clinical efficacy, and safety profile in patients with renal impairment. The literature indicates that severe renal impairment markedly prolongs the systemic retention of sugammadex and sugammadex–rocuronium. However, this pharmacokinetic alteration does not compromise the rapid reversal of neuromuscular blockade or increase the risk of recurarization or major adverse events. High-flux hemodialysis increases the clearance of sugammadex–rocuronium, but evidence supporting continuous renal replacement therapy and peritoneal dialysis remains limited. Overall, sugammadex may serve as an effective and generally well-tolerated reversal agent in carefully selected patients with severe renal impairment. Additional prospective studies are required to establish its long-term safety and guide clinical recommendations.